A design-led approach to transforming wicked problems into design situations and opportunities. (1st March 2019) - Bailey, Mark; Chatzakis, Emmanouil; Spencer, Nicholas; Lampitt Adey, Kate; Sterling, Nate; Smith, Neil
This article argues that using a design-led approach is highly beneficial when tackling complex problems to transform ambiguity into actionable design briefs and solution opportunities. This is evidenced by way of an ongoing project with a large public-sector organization. Northumbria University's School of Design academic experts use design-led approaches to innovation that promotes 'creative fusion' between diverse stakeholders in order to tackle 'wicked problems'. The authors continue this work as part of an Arts and Humanities Research Council/ European Regional Development Fund-funded programme entitled Creative Fuse North East (CFNE), involving five regional universities, of which the project discussed here is a part. The main objectives of CFNE are to develop and deploy approaches to innovation that apply skills from creative graduates to benefit the wider creative economy, address barriers to innovation and promote growth and sustainability within and without the Creative, Digital and IT sector (CDIT). The authors propose that to do this it is vital to convert stakeholders into co-creation activists empowered with the creative confidence and tools required to speculate about uncertain futures.